2019
DOI: 10.15275/rusomj.2019.0411
|View full text |Cite
|
Sign up to set email alerts
|

Influence of GSTP1 gene polymorhism on decreased semen quality

Abstract: Background ― Genetic polymorphisms analysis of metabolic and antioxidant systems pathway genes are associated with male infertility is the most perspective and developed field in andrology. Purpose ― the aim of the research is to reveal the association of the glutathione S-transferase gene GSTP1 polymorphism C/T (rs1138272) with risk of pathospermia in Russian men in Moscow region. Material and Methods ― Case control study was conducted on 68 fertile men and 70 infertile men with various forms of pathospermia.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
1
3
0
1
Order By: Relevance
“…We found a direct correlation between reproductive losses (spontaneous abortion in early pregnancy) and the level of DNA fragmentation (Fig. 1) tozoa in male infertility [6,10]. Palermo Gianpiero D. et al showed an inverse correlation between DNA fragmentation and sperm mobility [11].…”
Section: Introductionsupporting
confidence: 57%
“…We found a direct correlation between reproductive losses (spontaneous abortion in early pregnancy) and the level of DNA fragmentation (Fig. 1) tozoa in male infertility [6,10]. Palermo Gianpiero D. et al showed an inverse correlation between DNA fragmentation and sperm mobility [11].…”
Section: Introductionsupporting
confidence: 57%
“…Известно, что основная протективная роль при воздействии окислительного стресса принадлежит неферментативному звену антиоксидантов (глутатион, витамины А, Е), так и ферментативным антиоксидантам (супероксиддисмутаза (СОД), глутатионпероксидаза, каталаза) [23]. Результаты функционирования неферментативных и ферментативных антиоксидантных систем играют важную роль в регуляции канцерогенеза, в том числе, в процессах, стимулирующих прогрессию опухоли, а также формирование ее резистентности к проводимой терапии [14].…”
Section: Discussionunclassified
“…Due to chronic inflammation in the periodontal tissues, neutrophils and lymphocytes are activated enabling synthesis of cytokines and prostaglandins [2]. Long-term chronic inflammation in tissues leads to an increase in reactive oxygen species (ROS), and an imbalance in the antioxidant system [3,4]. The long-term chronic inflammation is known to facilitate destruction of tissues supporting teeth, including the gums, periodontal ligament, and alveolar bone [5].…”
Section: Introductionmentioning
confidence: 99%